Increased Fluid Administration After Early Acute Kidney Injury is Associated with Less Renal Recovery. Issue 5 (November 2015) - Raimundo, Mario; Crichton, Siobhan; Martin, John R.; Syed, Yadullah; Varrier, Matt; Wyncoll, Duncan; Ostermann, Marlies
ABSTRACT: Introduction: In acute kidney injury (AKI), fluid accumulation is associated with poor outcome. We aimed to determine whether fluid intake or output had the major role. Methods: Retrospective analysis of patients admitted to the Intensive Care Unit between July 2007 and June 2009 who had AKI stage I. We collected fluid input, output, and haemodynamic data on day of AKI I and on day of AKI III (if AKI III developed) or 72 h after AKI I (if patients did not progress to AKI III). Univariable and multivariable logistic regression analyses were performed. Results: Among 210 patients with AKI I (median age 70 y; 138 males), 85 had a subsequent mean fluid gain >1 L/day. Their risk of AKI III or death in intensive care unit was significantly higher compared with patients who gained ⩽1 L/day (63.5% vs. 23.3%, P = 0.001, and 43.5% vs. 24.8%, P = 0.004, respectively). AKI I patients who gained >1 L/day had a significantly lower urine output (50 vs. 66 mL/h, P = 0.02), lower mean arterial pressure (71 vs. 74 mmHg, P = 0.01), higher arterial lactate level (2.7 vs. 2.0 mmol/L, P < 0.001), and higher Sequential Organ Failure Assessment score (9.4 vs. 8.2, P = 0.002) on day of AKI I compared with those who gained ⩽1 L/day. Multivariable analysis showed that only fluid intake was independently associated with progression to AKI III (OR 1.8 per 1 L; 95% CI 1.1 – 8.8; P = 0.02), but reduced urine output was not an independent risk factor (OR 0.8; 95% CI 0.3 – 2.2; P = 0.6). Conclusion: Increased fluid intake in early AKI was an independent risk factor for AKI III.